ACCOUNTING KNOWLEDGE FOR SMALL AND MEDIUM MICRO ENTERPRISES (MSMEs) ON FINANCIAL STATEMENTS - Abdul Mannan; Muhammad Saddam; Alyaa Rihhida Tul’aisy; Khairil Fathir (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The emergence of MSME actors contributes to the Indonesian economy. But unfortunately, many MSME actors still have difficulties managing their finances. This is due to their lack of accounting knowledge, so it isn’t easy to make good financial reports. This study aims to see how the understanding of nutmeg SMEs regarding their expertise in accounting for financial statements. This research will then use a qualitative approach as the method. The data used in this study came from various studies and previous studies that are still relevant to this research. After the research data is collected, the data will be analyzed to find the results. This study found that there were financial reports or bookkeeping records by MSME actors even though the form was still relatively simple. Then because the level of education is still primarily low, these MSME actors still find it challenging to make excellent and standard financial reports.